Waspada Dunia Maya: Strategi Mengidentifikasi dan Mengatasi Hoaks - Firdayanti J. Umar; Martinihani Martinihani; Nur Riswandi Marsuki (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The rise of fake news or hoaxes circulating in Indonesia has now entered a disturbing stage. Hoaxes not only harm society but can also disrupt national development. The government has taken a stand to combat hoaxes. People who care about this problem are also starting to move. One of them is the Indonesian Anti-Defamation Community (Mafindo), whose strategy for involving the community in social movements like this is known as crowdsourcing. Mafindo implements this strategy to invite the public to work together to fight hoaxes. The large number of hoaxes cannot be overcome individually. Therefore, it is necessary to involve all parties to refute the various hoaxes circulating. By using in-depth interviews, observations and secondary data collection, researchers describe the characteristics of crowdsourcing carried out by Mafindo to limit the spread of hoaxes in Indonesia. Evaluate the communication strategies adopted The spread of false and hateful information on social media has become a serious problem that can affect the integrity and stability of the democratic process. communication to overcome the spread of hoaxes and hate speech. building community involvement and collaboration with the media so that local government communication strategies have a positive impact in reducing the spread of hoaxes and hate speech.